2006
DOI: 10.1158/1055-9965.epi-05-0487
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GSTM1 and GSTT1 Polymorphisms on Micronucleus Frequencies in Human Lymphocytes In vivo

Abstract: The influence of genetic polymorphisms in GSTM1 and GSTT1 genes on micronucleus frequencies in human peripheral blood lymphocytes was assessed through a pooled analysis of data from seven laboratories that did biomonitoring studies using the in vivo cytokinesis-block micronucleus assay. A total of 301 nonoccupationally exposed individuals (207 males and 94 females) and 343 workers (237 males and 106 females) occupationally exposed to known or suspected genotoxic substances were analyzed by Poisson regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 32 publications
4
24
1
Order By: Relevance
“…During the aging process, the enzymes involved in DNA repair become less and less common, which increases the susceptibility of cells to genotoxic agents. 31,32 Kirsch-Volders et al 33 suggested that flaws in the cellular defense systems that protect against DNA damage, as well as the reduced efficiency of DNA repair, can lead to an accumulation of mutations. These mutations, either in isolation or in combination with other age-related alterations, can contribute to aging and the development of age-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…During the aging process, the enzymes involved in DNA repair become less and less common, which increases the susceptibility of cells to genotoxic agents. 31,32 Kirsch-Volders et al 33 suggested that flaws in the cellular defense systems that protect against DNA damage, as well as the reduced efficiency of DNA repair, can lead to an accumulation of mutations. These mutations, either in isolation or in combination with other age-related alterations, can contribute to aging and the development of age-related illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency ratio (FR), its confidence interval (CI), and the corresponding P values were reported. For categorical variables, the FR indicates the proportional increase of the micronucleus frequency in the study group; for example, a FR of 1.21 for females versus males means a 21% increase of micronucleus frequency in females (35). In order not to ignore important risk factors in such an exploratory multivariate analysis, the test level was relaxed to 0.10 (as the default test level of stepwise linear regression model in SAS package is 0.15, not the usual 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetically, ageing is associated with a number of gross cellular changes, including altered size and morphology, genomic instability and changes in expression and proliferation (Bolognesi et al, 1999;Zietkiewicz et al, 2009). It has been shown that a higher MN frequency is directly associated with decreased efficiency of DNA repair and increased genome instability (Kirsch-Volders et al, 2006;Orsière et al, 2006). The data has shown a significant increase of MN in lymphocytes in the exposed group.…”
Section: Discussionmentioning
confidence: 99%